Solvable groups of finite non-abelian sectional rank - Dashkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study non-Abelian solvable groups of finite non-Abelian sectional rank and prove that their (special) rank is finite.